Internalization Of Resilience Values In Islamic Religious Education Learning - Haryanti, Tutik; Tohirin, Tohirin; Anwar, Khairil (-, 2024)
This article aims to discuss the importance of internalizing resilience values in Islamic Religious Education (PAI) learning at state junior high schools in East Bintan District. Resilience, as the ability to rise from various life challenges, has a very significant role in shaping students' character and personality. Through the PAI approach, resilience values can be instilled by utilizing Islamic teachings which emphasize steadfastness, patience and sincerity in facing life's trials. Using a qualitative descriptive approach, this article explains how PAI teachers can integrate resilience values through teaching methods that involve modeling, providing motivation, and using relevant religious texts. Apart from that, this article also describes the benefits of internalizing resilience in helping students develop positive attitudes, manage stress, and foster enthusiasm to continue learning even when faced with difficulties. In conclusion, the internalization of resilience values in PAI not only strengthens students' religious aspects, but also forms a generation that is more resilient in facing life's challenges.